2022
DOI: 10.1039/d2fo01438f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the multi-physiological and functional mechanism of wheat alkylresorcinols based on reverse molecular docking and network pharmacology

Abstract: Alkylresorcinols (ARs) are phenolic lipids present in the bran part of whole grain wheat and rye, which possess antioxidant, anti-inflammatory, anti-cancer and anti-tumor properties. The physiological activities of ARs have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…Alkylresorcinols are phenolic lipids widely distributed in plants and bacteria. Different degrees of substitution yield various compounds that have been reported to possess antioxidant (Gliwa et al, 2011), anti-inflammatory (Wei et al, 2022), antimicrobial and antitumor activities. Given a variety of alkylresorcinols compounds have antimicrobial activity, it is possible to conclude that these compounds act as defensive agents in plants.…”
Section: A B Figurementioning
confidence: 99%
“…Alkylresorcinols are phenolic lipids widely distributed in plants and bacteria. Different degrees of substitution yield various compounds that have been reported to possess antioxidant (Gliwa et al, 2011), anti-inflammatory (Wei et al, 2022), antimicrobial and antitumor activities. Given a variety of alkylresorcinols compounds have antimicrobial activity, it is possible to conclude that these compounds act as defensive agents in plants.…”
Section: A B Figurementioning
confidence: 99%
“…ADMET analysis is an important tool in drug discovery [ 19 , 20 ]. We performed ADMET analysis on compound P3 using the ADMET-AI platform, and the results showed that compound P3 has excellent pharmacokinetic properties.…”
Section: Resultsmentioning
confidence: 99%